On the fabrication of finer grain structure through using finer wire diameter for wire arc additive manufacturing of AZ31B magnesium alloy - Jae-Deuk Kim; Jooyong Cheon; Yeong-Do Park; Yang-Do Kim; Changwook Ji (Journal of Materials Research and Technology, 2024)
Magnesium (Mg) alloys are the lightest structural metallic material, but it is hard to be applied to various industrial fields due to the crystallographic nature that is composed with hexagonal closed packed (HCP). Wire arc additive manufacturing (WAAM) could be a key to fabricating Mg parts with large sizes and complex designs. It has numerous advantages such as high material efficiency, short-delivery time by faster manufacturing speed, easy to modify, etc. Yet, most of the research mentioned the grain coarsening and degradation in mechanical properties when fabricating WAAM products using Mg alloy wires. To solve the problems, a solution was suggested with supposition that the lessen the deposit metal size a little by changing to the finer wire diameter can reduce the actual heat input and heat accumulation during the WAAM process. In this research, the WAAM of AZ31B has been conducted using a wire diameter of 1.0 mm rather using the 1.2 mm that is used in common. It was found that the finer (about 90 %) and equiaxed microstructure was composing the WAAM product made of wire diameter of 1.0 mm, and it results in about two times higher mechanical strength.